Evaluating sampling strategies for enzootic Venezuelan equine encephalitis virus vectors in Florida and Panama - Kristin E. Sloyer; Mileyka Santos; Eddier Rivera; Lawrence E. Reeves; Jean Paul Carrera; Amy Y. Vittor; Anayansi Valderrama; Nathan D. Burkett-Cadena (Public Library of Science (PLoS), 2022)
Determining effective sampling methods for mosquitoes are among the first objectives in elucidating transmission cycles of vector-borne zoonotic disease, as the effectiveness of sampling methods can differ based on species, location, and physiological state. The Spissipes section of the subgenus Melanoconion of Culex represents an understudied group of mosquitoes which transmit Venezuelan equine encephalitis viruses (VEEV) in the Western Hemisphere. The objective of this study was to determine effective collection methods that target both blood-engorged and non-engorged females of the Spissipes section of Culex subgenus Melanoconion to test the hypothesis that favorable trapping methods differ between species and by physiological status within a species. Mosquitoes were collected using two commercially available traps, (CDC-light trap and BG-Sentinel trap), two novel passive traps (a novel mosquito drift fence and pop-up resting shelters), and two novel aspirators, (a small-diameter aspirator and a large-diameter aspirator) in Darién, Panama, and Florida, USA. The total number of female mosquitoes collected for each species was compared using rarefaction curves and diversity metrics. We also compared the utility of each trap for collecting total females and blood-engorged females of four Spissipes section mosquito species in Florida and Darién. In Darién, it was found that both blood-engorged and unfed females of Cx. pedroi were most effectively collected using the mosquito drift fence at 57.6% and 61.7% respectively. In contrast, the most unfed Cx. spissipes were collected using the mosquito drift fence (40.7%) while blood-engorged females were collected effectively by pop-up resting shelters (42.3%). In Florida, the best sampling technique for the collection of blood-engorged Cx. panocossa was the large diameter aspirator at 41.9%, while the best trap for collecting Cx. cedecei was the pop-up resting shelter at 45.9%. For unfed female Spissipes section mosquitoes in Florida, the CDC light trap with CO2 collected 84.5% and 98.3% of Cx. cedecei and Cx. panocossa respectively in Florida. Rarefaction analysis, and both the Shannon and Simpsons diversity indices all demonstrated that the mosquito drift fence was capable of collecting the greatest diversity of mosquito species regardless of location. The finding that the proportions of unfed and blood-engorged mosquitoes collected by traps differed both among and between species has implications for how studies of VEEV vectors will be carried out in future investigations. In Florida a combination of pop-up resting shelters and use of a large-diameter aspirator would be optimal for the collection of both VEEV vectors for host-use studies. Results demonstrate that traps can be constructed from common materials to collect mosquitoes for VEEV vector studies and could be assessed for their utilization in vectors of other systems as well. Unfortunately, no single method was effective for capturing all species and physiological states, highlighting a particular need for assessing trap utility for target species of a study. Author summary Venezuelan equine encephalitis virus is a potentially deadly human pathogen that is transmitted by an understudied group of tropical mosquitoes (Spissipes section of the Culex subgenus Melanoconion). These mosquitoes reside in swamps and jungles, and are challenging to identify, so studying their biology and importance in transmitting VEEV has been neglected. To further our understanding of VEEV, we compared six novel and commercially available traps to determine which traps are best for capturing these species in Panama and Florida. We found that several different types of traps are effective for collecting blood-engorged females of different species of VEEV vectors, and that traps utilized for collecting unfed specimens are not necessarily the same traps one should use for collecting blood-engorged females of the same species. Results of this study will enable researchers to better capture these important disease vectors, particularly those that are blood-engorged, which will allow researchers to determine host associations necessary for understanding VEEV transmission. This information can be used to make decisions on controlling vector species.